Exploration of the value of concurrent chemotherapy for T2N1 nasopharyngeal carcinoma under intensity modulated radiotherapy mode - Liao, Kai; Zhang, Jian; Qiu, Wenze; Zheng, Ronghui (Frontiers in Oncology, 2024)
ProblemIn the era of intensity-modulated radiation therapy (IMRT), the status of concurrent chemoradiotherapy(CCRT) for stage II nasopharyngeal carcinoma(NPC), particularly for patients in T2N1 subtype, remains controversial nowadays.AimThis study exclusively aims to explore the value of concurrent chemotherapy in the treatment of T2N1 NPC under IMRT mode.MethodsA retrospective analysis was conducted on 218 cases of T2N1 NPC patients treated at our hospital from January 2015 to December 2020, comprising 75 cases treated with IMRT and 143 cases treated with CCRT. The study compared therapeutic outcomes and side effects between the two groups.ResultsThe 5-year progression-free survival (PFS), overall survival (OS), locoregional relapse-free survival (LRRFS) and,distant metastasis-free survival (DMFS) estimated by the K-M method for the IMRT vs. CCRT groups were 86.1% vs. 85.1%,89.3% vs. 87.9%, 95.9% vs. 94.9%,and 90.2% vs. 89.1%, respectively, with no statistically significant differences (Log-rank P>0.05 for all comparisons). Cox regression analysis identified Epstein-Barr virus (EBV) DNA copy level (≥1000 vs. <1000 copies/ml)(the cutoff value was determined through the ROC curve), lymph node necrosis (yes vs. no) and extra-nodal extension (yes vs. no) as independent prognostic factors for PFS(P<0.05 for all comparisons). Subgroup analysis indicated an interaction effect between lymph node necrosis (yes vs. no) and treatment modality (IMRT vs. CCRT) regarding PFS (P for interaction<0.05). In the subgroup with lymph node necrosis, IMRT compared to CCRT had a poorer prognosis (HR: 1.85,95% CI: 1.02-3.50). CCRT was noted to increase acute hematological, gastrointestinal and other toxicities.ConclusionsThis study provides a reference for clinical treatment decisions in T2N1 NPC. For the entire population of T2N1 NPC, the therapeutic effects of IMRT and CCRT are comparable, with increased acute toxicities in the latter. However, for patients with EBV-DNA copy level ≥1000 copies/ml, lymph node necrosis and extra-nodal extension, CCRT may be considered as appropriate. Particularly, patients with lymph node necrosis may be potential beneficiaries for CCRT.